Benefits of treatment with ASTENALT® in reducing video display terminal-induced asthenopia. - Basile, Andrea; Cendali, Magda; Ciacci, David; Jonsson, Francesca; Mandelli, Giulia (Infocus (2035-0252), 2024)
Asthenopia is a condition that is frequently encountered after the use of digital devices, and it is also known as "video display terminal (VDT)-induced asthenopia" or simply "VDT asthenopia". A group of healthy video display terminal workers, all with a corrected or uncorrected visual acuity of 10/10 and no tear dysfunction or systemic or ocular disorders at enrolment was selected for this study conducted over a 2-month period. The study aimed to assess, in patients with over 6 hours exposure to a video display terminal, the effectiveness of the food supplement ASTENALT® in alleviating the symptoms of asthenopia. ASTENALT® is based on magnesium citrate and dry extract of Ashwagandha and blueberry, and it contains EYEMUSE®, heat-inactivated Lacticaseibacillus paracasei KW 3110, a clinically tested lactic acid bacteria developed by Kirin Holdings Co., Ltd. From a total of approximately 100 patients assessed, we selected a sample of 25 patients who used the product ASTENALT® to evaluate the objective and subjective improvements obtained. The study was completed by 20 patients who complied with the prescribed protocol. Assessments were carried out using specific eye tests and dedicated questionnaires. At 60 days, treatment response and tolerability of the supplement were very good in the majority of patients, who reported a marked improvement of the subjective symptoms of VDT asthenopia.